Beer produced via hydrodynamic cavitation retains higher amounts of xanthohumol and other hops prenylflavonoids. (May 2018) - Ciriminna, Rosaria; Albanese, Lorenzo; Di Stefano, Vita; Delisi, Riccardo; Avellone, Giuseppe; Meneguzzo, Francesco; Pagliaro, Mario
Abstract: Some of the most valuable bioactive compounds in beer comes from hops polyphenols, mainly flavonoids, some of which are unique to inflorescences of that flowering plant. Although far from pharmacologically relevant concentrations, low doses of xanthohumol and related prenylflavonoids found in beer contribute to the overall antioxidant activity of the product, as well as to significant chemopreventive action about certain diseases, such as cardiovascular, neurodegenerative, and some cancer types. Hence, the efforts to explore both ingredients and brewing methods aimed at enhancing the concentration of such bioactive compounds. In this study, a novel brewing method assisted by hydrodynamic cavitation was experimented, proving its ability to retain or generate higher amounts of xanthohumol, desmethylxanthohumol and 6-geranylnaringenin. Operational parameters, concerning hops processing, and leading to the enhanced retention, or generation, of the considered prenylflavonoids, were found to be common to all those same compounds. As well, basic mechanisms were hypothesized, such as increased extraction from hops, reduced adsorption to insoluble malt proteins, and reduced isomerization. The results expand recent evidence about enhanced extraction of bioactive compounds by processes based on hydrodynamic cavitation, as well as add to already proven benefits of hydrodynamic cavitation to the brewing processes. Graphical abstract: Highlights: HC-assisted brewing enhances concentration of hops prenylflavonoids in beer. Time-temperature quantitative limits for HC-assisted hops processing are identified. Enhanced extraction, and reduced adsorption to insoluble proteins, are hypothesized. HC surprisingly effective in generating the prenylated flavanone 6-GN. HC-assisted beer brewing promising for further enrichment with prenylflavonoids.